Instructed pragmatics at a glance: Where instructional studies were, are, and should be going. (9th January 2015) - Taguchi, Naoko
<x content-type="archive" xml:space="preserve">Abstract</x> This paper brings together the research and developments of instructed pragmatics over the past three decades by reporting the synthesis findings of instructional intervention studies in interlanguage pragmatics. Two questions have guided this investigation: (1) is instruction effective in learning pragmatics?; and (2) what methods are most effective in learning pragmatics? Exhaustive electronic bibliographical searches yielded a body of 58 instructional intervention studies for the review. Findings across these studies are compared and explored for common patterns and inconsistencies that emerge among them. The paper concludes with implications for future research based on the survey of the existing practice.